Regulação jurídica da destinação de resíduos de saúde: estudo de caso sobre a eficácia normativa na proteção ambiental em hospital de joão pessoa-PB - Cunha, Fábio Leandro de Alencar (My University, 2025)
The 1988 Federal Constitution of Brazil enshrines the environment as a fundamental right, assigning both the State and society the responsibility for its protection. In the context of public health, the proper management of Healthcare Waste (HCW) is essential not only to ensure sanitary safety but also to preserve environmental integrity. The correct segregation, packaging, storage, and final disposal of HCW is mandated by several legal regulations, such as ANVISA Resolution RDC No. 222/2018 and the National Solid Waste Policy (Law No. 12,305/2010). However, many healthcare institutions still face challenges in effectively implementing and monitoring these legal requirements. In this context, the present dissertation aims to analyze the effectiveness of legal regulation and waste disposal practices in a hospital located in João Pessoa, Paraíba (PB), investigating the main challenges faced in HCW management, its environmental and health impacts, and proposing viable solutions to improve such management. To achieve this, a qualitative case study with a descriptive and exploratory character was conducted at Hospital Nossa Senhora das Neves (HNSN), a reference medical institution in João Pessoa. Data collection involved document analysis of the Healthcare Waste Management Plan (PGRSS), interviews with hospital managers and technicians, on-site visits with photographic documentation, and the application of an evaluation instrument based on current legislation. The results showed that HNSN has an implemented PGRSS, with established routines for segregation, packaging, and storage of waste. The institution operates internal and external temporary storage shelters organized by waste group (general, infectious, and chemical), and employs technologies such as solidifiers for liquid waste. However, significant shortcomings were identified, including the absence of a legally qualified environmental professional as the plan?s responsible technician, lack of documented environmental licensing for both the hospital and its third-party service provider, the absence of an environmental monitoring program, and a lack of performance indicators. In addition, improper placement of general waste containers in sensitive areas?such as near refrigerators in inpatient suites?was observed, violating ANVISA regulations. In conclusion, despite some progress in HCW management, the hospital exhibits structural and regulatory weaknesses that hinder the full effectiveness of its PGRSS. It is recommended that the plan be revised to include performance indicators, the formal designation of a qualified environmental professional, detailed training actions, and the implementation of a continuous environmental education and monitoring program. These measures are essential to ensure legal compliance and promote more sustainable practices. [resumo fornecido pelo autor]
A Constituição Federal de 1988 consagra o meio ambiente como um direito fundamental, conferindo ao Estado e à sociedade a responsabilidade pela sua proteção. No contexto da saúde pública, a gestão adequada dos Resíduos de Serviços de Saúde (RSS) é essencial não apenas para garantir a segurança sanitária, mas também para assegurar a integridade ambiental. A correta segregação, acondicionamento, armazenamento e destinação final dos RSS é determinada por uma série de normativas legais, como a Resolução RDC nº 222/2018 da ANVISA e a Política Nacional de Resíduos Sólidos (Lei nº 12.305/2010). Entretanto, diversos estabelecimentos de saúde ainda enfrentam dificuldades na implementação e monitoramento efetivo dessas exigências legais. Diante disso, a presente dissertação tem como objetivo analisar a eficácia da regulação jurídica e das práticas de destinação de resíduos de saúde em um hospital localizado em João Pessoa - PB, investigando os principais desafios enfrentados no gerenciamento de RSS, seus impactos ambientais e sanitários, bem como propor soluções viáveis para o aprimoramento dessa gestão. Para tanto, foi realizado um estudo de caso, qualitativo, com caráter descritivo e exploratório, desenvolvido no Hospital Nossa Senhora das Neves (HNSN), referência no atendimento médico-hospitalar na cidade de João Pessoa. A coleta de dados ocorreu por meio da análise documental do Plano de Gerenciamento de Resíduos de Serviços de Saúde (PGRSS), entrevistas com gestores e técnicos da instituição, visitas técnicas com registro fotográfico e aplicação de um instrumento de avaliação baseado nas legislações vigentes. Os resultados mostraram que o HNSN possui um PGRSS implantado, com rotinas estabelecidas de segregação, acondicionamento e armazenamento dos resíduos. A instituição conta com abrigos temporários internos e externos organizados por grupo de resíduo (comuns, infectantes e químicos), e utiliza tecnologias como solidificadores para resíduos líquidos. No entanto, foram identificadas algumas falhas, como a ausência de um profissional técnico ambiental legalmente habilitado como responsável pelo plano, falta de comprovação documental do licenciamento ambiental da unidade e da empresa terceirizada, inexistência de programa de monitoramento ambiental e ausência de indicadores de desempenho. Também se observou o posicionamento inadequado de recipientes de resíduos comuns em áreas sensíveis, como próximas a frigobares em suítes de internação, contrariando normas da ANVISA. Conclui-se que, apesar dos avanços pontuais na gestão de RSS, o hospital apresenta fragilidades estruturais e normativas que comprometem a plena eficácia do PGRSS. Recomenda-se a revisão do plano com inclusão de indicadores, designação formal de responsável técnico habilitado, detalhamento das ações de capacitação e implementação de um programa contínuo de educação ambiental e monitoramento. Tais medidas são fundamentais para assegurar a conformidade com as exigências legais e promover práticas mais sustentáveis. [resumo fornecido pelo autor]
Keywords: Direito ambiental; Resíduos de serviços de saúde; Gestão ambiental; Meio ambiente - Legislação; Brasil. [Constituição (1988)]; Hospitais - João Pessoa (PB) - Eliminação de resíduos; Environmental law; Medical wastes; Environmental management; Environment - Legislation; Brazil. [Constitution (1988)]; Hospitals - João Pessoa (Brazil) - Waste disposal